EQUIVALENT LOAD METHOD FOR FATIGUE LIFE ANALYSIS OF LUGS UNDER OBLIQUE LOADING - LI YanBin; DONG DengKe; GONG YunZhao (Jixie qiangdu)
First of all,stress analysis of lug under different loading angles was carried out. For the fatigue life analysis of lug under tension-compression loads,the compression load was treated equivalently,and the effective equivalent load factor λ was obtained. The fatigue load spectrum was equivalent to Pmax λPmin,and then the fatigue life of lug structure was obtained by the Detail Fatigue Rating（ DFR） method. Finally,the method was proved by the fatigue test of lug in 45° angles load,which proves that the method is practical in engineering.